THE ENGLISH AS FOREIGN LANGUAGE (EFL) STUDENTS’ PERSPECTIVES ON THE READING EDUCATIONAL COMICS BASED ON LOCAL WISDOM “THE STORY OF CANDI PARI - Nadliyah Putri Syalwa; Vidya Mandarani; Yuli Astutik (Universitas Muhammadiyah Metro, 2026)
This qualitative study explores seventh-grade students' perspectives on using